Practical Manual of Microbiology - Sundara Rajan (Anmol Publications Pvt, 2001)
Introduction, microscopy, laboratory equipements, cleaning of glassware and sterilization, culture media, preparation of stains, staining of microbes, , types studies, helminthes.